Controlling the velocities and the number of emitted particles in the tunneling to open space dynamics - Lode, Axel U. J.; Klaiman, Shachar; Alon, Ofir E.; Streltsov, Alexej Iwanowitsch; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2014)
A scheme to control the many-boson tunneling process from a trap through a potential barrier to open space is devised and demonstrated. The number of ejected particles and their velocities can be controlled by two parameters, the threshold of the potential and the interparticle interaction. Employing a recently developed efficient many-body method, results for two, three, and one hundred interacting bosons in one spatial dimension can be computed numerically exactly, solving thereby an intricate problem of general interest. It is shown that the control scheme devised for the many-boson tunneling process performs very well for the dynamics of the momentum density, the correlations, and the coherence, as well as for the number of particles remaining in the trap. To interpret the many-body tunneling process, a transparent model assembling the many-body process from single-particle emission processes is derived. Analysis of the energetics of available decay channels together with the numerical results rules out the situation of two (or more) bosons tunneling together to open space. The present investigation generalizes the findings reported by us [Proc. Natl. Acad. Sci. USA 109, 13521 (2012)] for many-boson tunneling to open space in the absence of a threshold.